Iron oxide nanoparticles: synthesis, functionalization, and applications in diagnosis and treatment of cancer - Hernández-Hernández, Aldahir A.; Aguirre-Álvarez, Gabriel; Cariño-Cortés, Raquel; Mendoza-Huizar, Luis H.; Jiménez-Alvarado, Rubén (Chemical papers, 2020)
In recent years, iron oxide nanoparticles have demonstrated great potential in biomedical applications due to their non-toxic role in biological systems. Also, the magnetic and semiconductor properties of iron oxide nanoparticles can lead to multifunctional applications in medicine. These nanoparticles have been developed as antibacterial, antifungal, and anticancer. For cancer treatment and diagnosis, iron oxide nanoparticles have been functionalized with drugs. However, many of those drugs have been related to adverse effects on health. On the other hand, phytochemicals from extracts of plants have been used as an alternative for the functionalization of these nanoparticles preventing negative effects. The main advantage of these nanoparticles is the high biodistribution in the organism compared with other drug delivery systems. The magnetism of iron oxide nanoparticles has been used in cancer treatment and diagnosis, for example, thermoablation, hyperthermia, and contrast media in magnetic resonance imaging. Therefore, this work aimed to discuss the methods for the synthesis of iron oxide nanoparticles, the different kinds of coatings used to functionalize them, and the different applications they have had in cancer treatment and diagnosis.